Ruang Lingkup Pendidikan: Pengaplikasian Maqasid Syariah Kajian dalam Fikih Pada Siswa di SMAN 1 Purwokerto - Karuniawan, Iing Ilham; Roqib, Moh. (LPPM Institut Pendidikan Nusantara Global, 2024)
Education is the main foundation in the formation of individuals with quality and integrity in society. One approach that can be applied is the application of Maqasid Syariah in the study of jurisprudence for students at SMAN 1 Purwokerto.This article discusses the application of Maqasid Syariah in fiqh and utilizes the concept of maqasid sharia. Maqasid Syariah is an approach that emphasizes the core or substance means of law in Islam, therefore maqasid sharia more clearly identifies Islam. matters related to fiqh will be clear when applied through the maqasid sharia method will open up a broader and deeper interpretation of Islamic law.This research aims to explore the scope of application of Maqasid Syariah in fiqh learning in senior high schools. The study employed descriptive analysis utilizing a qualitative methodology, involving literature study and interviews with teachers and students. The findings indicate that implementing Maqasid Syariah in fiqh education at SMAN 1 Purwokerto positively influences the development of students' character and enhances their comprehension of Islamic teachings. The implication of this research is the need to develop a curriculum that integrates Maqasid Syariah principles as part of Islamic education in schools to support the formation of a generation that is responsible and has noble character in society. Through this analysis, this article offers a summary of the significance of comprehending implementing maqasid sharia in facing changing times and the complexity of contemporary problems in Muslim society.